The day after tomorrow - April, Renée; Brenner, David; Chusid, Barry; Emmerich, Roland; Gordon, Mark, 1956-; Gyllenhaal, Jake, 1980-; Kloser, Harald, 1956-; Mihok, Dash, 1974-; Nachmanoff, Jeffrey; Nichols, Austin, 1980-; Quaid, Dennis; Rossum, Emmy, 1986-; et al. ([United States] : 20th Century Fox Home Entertainment, 2004)
Cuando el calentamiento global provoca la aparición de una nueva Edad de Hielo, tornados arrasan Los Ángeles, un maremoto envuelve Nueva York y todo el hemisferio norte comienza a congelarse. Ahora, el climatólogo Jack Hall, su hijo Sam, y un pequeño grupo de sobrevivientes deberán sobrellevar la supertormenta creciete y mantenerse vivos en la cara de un enemigo más poderoso e implacable que nadie lo ha visto en su vida: la Madre Naturaleza.
Material extra: commentary by director Roland Emmerich and producer Mark Gordon; commentary by writer Jeffrey Nachmanoff, cinematographer Ueli Steiger, editor David Brenner, and production designer Barry Chusid; deleted scenes; interactive audio demo; DVD-ROM link to hour-long exclusive material.
Título del envase.
Director of photography, Ueli Steiger ; editor, David Brenner ; music, Harald Kloser ; costume designer, Renée April ; production designer, Barry Chusid ; visual effects supervisors, Greg Anderson ... [et al.].
Dennis Quaid, Jake Gyllenhaal, Emmy Rossum, Dash Mihok, Jay O. Sanders, Sela Ward, Austin Nichols, Arjay Smith, Tamlyn Tomita.
MPAA rating: PG-13; for intense situations of peril.
DVD, region 1, widescreen presentation; Dolby Digital.
Keywords: Calentamiento global -- Teatro; Películas cinematográficas; Periodos glaciares -- Teatro